Capacity of the common Arctic picoeukaryote Micromonas to adapt to a warming ocean. Issue 2 (2nd December 2019) - Benner, Ina; Irwin, Andrew J.; Finkel, Zoe V.
Abstract: Phytoplankton are sensitive to temperature and other environmental conditions expected to change with warming over the next century. We quantified the capacity of an ecologically dominant Arctic phytoplankton species, Micromonas polaris, to adapt to changes in temperature, increased temperature and irradiance, and increased temperature and periodic nitrogen starvation, over several hundred generations. When originally isolated, this strain of Micromonas had its maximum growth rate at 6°C, and its growth rate declined above 10°C. We find an evolutionary increase in growth rate, with the largest increases associated with the elevated temperature treatments, especially when combined with repeated nitrate starvation. After several hundred generations of exposure, the growth rate of Micromonas under 13°C almost doubled and was higher than under 6°C. This increase in growth rate is consistent with the Arrhenius model of temperature effects on metabolism and suggests a general hypothesis for the evolutionary potential of phytoplankton to respond evolutionarily to temperature change.